Small Claim Court as the Alternative of Bad Credit Settlement for Legal Certainty of the Economic Actors - Pujiyono, Pujiyono; Pati, Umi Khaerah; Pranoto, Pranoto; Tejomurti, Kukuh (Universitas Negeri Semarang, 2021)
This article aimed to analyze the problem of legal cases accumulation, especially default on credit contracts in court. It also analyzes the effectiveness of implementing a small claim court in contract default and the independence of a single judge in handling cases through the small claim court mechanism. Small claim court also to offer a breakthrough in the settlement of bad loans related to contract defaults to reduce the burden on courts in Indonesia and provide legal certainty to business actors. The sole judge also examine, resolve and decide on inheritance cases in a fast and efficient process to issue a fair decision for all parties. This normative study was carried out using statutory, case, comparative law, and analysis content approaches. The research results showed that the filing of small claim court increased 10 times from 2015 to 2020, with the plaintiffs dominated by banks in bad credit cases. A small claim court provides benefits the bank and the customer because it speeds up the settlement of the plaintiff's money in a bad credit case with a case value of not more than 500 million, especially for microloans in a maximum period of 25 days. Furthermore, the latest regulation of 2019 concerning small claim court gives judges the authority to confiscate guarantees and conduct auctions to carry out forced executions through the Court Execution Auction process.